A randomized controlled trial comparing the efficacy of 1-L polyethylene glycol solution with ascorbic acid plus prucalopride versus 2-L polyethylene glycol solution with ascorbic acid for bowel preparation. (2nd December 2018) - Choi, Seong Ji; Kim, Eun Sun; Choi, Byeong Kwang; Min, Geeho; Kim, Woojung; Lee, Jung Min; Lee, Jae Min; Kim, Seung Han; Choi, Hyuk Soon; Keum, Bora; Jeen, Yoon Tae; Lee, Hong Sik; et al.
Abstract: Objectives: Bowel cleansing is a major patient complaint during colonoscopy. Adding laxatives to the bowel preparation is effective in replacing a portion of bowel preparation solution and reducing its volume. Prucalopride is a serotonin receptor agonist that stimulates gastrointestinal motility and provides propulsive force for defecation. This study aimed to compare 1 L polyethylene glycol (PEG) with ascorbic acid (Asc) plus 2 mg prucalopride (1LP/AP) and 2 L PEG with Asc (2LP/A) for colonoscopy preparation with respect to bowel-cleansing quality and side effects. Methods: A single-center, randomized, prospective study was conducted with 260 outpatients administered either 1LP/AP or 2LP/A. The primary endpoint was bowel preparation quality, which was evaluated using the Boston Bowel Preparation Scale and Aronchick Bowel Preparation Scale, and the secondary endpoints were patient tolerability and acceptability, assessed by a questionnaire-based survey. Results: The adequate bowel preparation rates were 88.5% and 83.1% in the 2LP/A and 1LP/AP groups, respectively, and the efficacy of 1LP/AP was equivalent to the control regimen ( p =.216). Other colonoscopic variables including adenoma detection rate were similar in both groups. Patient tolerability and acceptability were not significantly different, but patients in the 1LP/AP group were more willing to repeat the same regimen ( p =.039). Conclusions: Bowel preparation quality with 1LP/AP was equivalent to that with 2LP/A, which did not increase the occurrence of side effects, but it reduced the volume of the solution ingested, and increased patient satisfaction.